2018
DOI: 10.1007/s12020-018-1614-4
|View full text |Cite
|
Sign up to set email alerts
|

Voice quality preservation in thyroid surgery with neuromonitoring

Abstract: PurposeVoice problems are common after thyroidectomy. The aim of this study was to assess the voice related quality of life after thyroidectomy with neuromonitoring. The sociodemographic and treatment factors influencing the quality of voice after the operation were investigated.MethodsA total of 40 patients after thyroidectomy with neuromonitoring were enrolled into the study. The voice outcome was analyzed pre and postoperatively by two validated self-assessment questionnaires: Voice Handicap Index and Voice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…A partial scoring (0-40 points) for each one of the three subscales and one total score (0-120 points) is obtained (20). A total score between 0 and 30 reflects minimal handicap due to a voice problem; 31-60 is moderate and 61-120 is severe (21).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A partial scoring (0-40 points) for each one of the three subscales and one total score (0-120 points) is obtained (20). A total score between 0 and 30 reflects minimal handicap due to a voice problem; 31-60 is moderate and 61-120 is severe (21).…”
Section: Methodsmentioning
confidence: 99%
“…20 A total score between 0 and 30 reflects minimal handicap due to a voice problem; 31-60 is moderate and 61-120 is severe. 21 Two weeks after surgery, patients with postoperative VFP and 20 randomly selected control patients underwent a second voice recording, which was performed by a speech and language therapist at the Department of Phoniatrics. The voice samples were simultaneously recorded using the iPad system and a condenser microphone compatible with MDVP software, to validate the voice recording method used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…To explain this large number of patients with altered voices but functional nerves according to the neuromonitoring, several reasons could be put forward (that can be limitations of our study). The combination of subjective and objective variables to detect impaired voices further improved sensitivity, compared to other studies using only subjective evaluation criteria may be one possible explanation [2,8,12,13]. The short time between surgery and postoperative ENT evaluation at 3 months also overestimated the percentage of post-thyroid vocal impairment.…”
Section: Discussionmentioning
confidence: 86%
“…Very few studies presented results with intraoperative monitoring of lower and upper laryngeal nerves in such a population with subjective and objective evaluation criteria [12][13][14]. Grouping three scores including subjective and objective evaluation variables allowed us to prioritize sensitivity to specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with unilateral recurrent laryngeal nerve palsy may not have serious respiratory difficulties; however, some problems with voice quality and hoarseness might be observed. 37 Some previous studies showed no significant differences in the complication rates and postsurgical calcium levels between OT and "modern" techniques. 38,39 Surgeons' experience using RT and ET has become sufficient to produce a low complication rate and very high oncological efficacy rate.…”
Section: Postsurgical Complicationsmentioning
confidence: 90%